2020
DOI: 10.1038/s41467-020-14756-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically-stable ligands bridge the photoluminescence-electroluminescence gap of quantum dots

Abstract: Colloidal quantum dots are promising emitters for quantum-dot-based light-emitting-diodes. Though quantum dots have been synthesized with efficient, stable, and high colour-purity photoluminescence, inheriting their superior luminescent properties in light-emitting-diodes remains challenging. This is commonly attributed to unbalanced charge injection and/or interfacial exciton quenching in the devices. Here, a general but previously overlooked degradation channel in light-emitting-diodes, i.e., operando electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
231
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(239 citation statements)
references
References 50 publications
8
231
0
Order By: Relevance
“…It is interesting to observe that the inorganic–organic interface for the QDs to be applied for ECL generation needed to be different from that applied for electroluminescence in light-emitting-diodes. For the QDs in light-emitting-diodes, a recent publication 9 revealed that, for highly photoluminescent CdSe/CdS/ZnS core/shell/shell QDs, the inorganic–organic interface should not have excess zinc cations in the form of carboxylate salts. Otherwise, the light-emitting-diodes would become extremely inefficient and unstable in operation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to observe that the inorganic–organic interface for the QDs to be applied for ECL generation needed to be different from that applied for electroluminescence in light-emitting-diodes. For the QDs in light-emitting-diodes, a recent publication 9 revealed that, for highly photoluminescent CdSe/CdS/ZnS core/shell/shell QDs, the inorganic–organic interface should not have excess zinc cations in the form of carboxylate salts. Otherwise, the light-emitting-diodes would become extremely inefficient and unstable in operation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Different from ECL generation, the CdSe/CdS/ZnS core/shell/shell QDs have no comparative advantages over the CdSe/CdS core/shell ones on efficiency of light-emitting-diodes. 9 Furthermore, requirements of the inorganic–organic interface of the QDs for ECL and electroluminescence differ from each other drastically. Overall, these results suggest that, for a specific application—including ECL and light-emitting-diodes—of QDs, tailored design of QDs is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…52 The multiple QD-LED devices were interconnected by the transparent ICL. This device exhibited Pu et al 26 CdSe Electrochemically stable ligands T95@1,000 cd/m 2 > 3,800 hours for red T50@100 cd/m 2 > 10,000 hours for blue Won et al 31 InP-red HF-based surface etching for effective shell coating PLQY 98%, EQE 21.4%, T50@100 cd/m 2 > 1,000,000 hours Kim et al 32 InP 49 Typical structure Al-doped ZnO NP for ETL -Dai et al 51 Typical structure PMMA hole blocking layer EQE 20.5%, turn-on voltage 1.7 V, T50@100cd/m2 100,000 hours Sun et al 28 Inverted structure IML between ZnO/QD layers EQE 13.57% Lee et al 51 Inverted structure EDTA between ZnO/QD layers Luminance 187,186 cd/m2, EQE 5.5% Zhang et al 52 Tandem structure Stacking multiple QD-LED devices Current efficiency 41.5 cd/A, EQE 23.1% for red Current efficiency 121.5 cd/A, EQE 27.6% for green Current efficiency 17.9 cd/A, EQE 21.4% for blue Fabrication Process Coe-Sullivan et al 58 Spin-coating Phase separation during spincoating process…”
Section: Device Architecture Of Qd-ledmentioning
confidence: 91%
“…Pu et al reported the electrochemically stable surfacebinding ligand concept. 26 The QD layer can be degraded through an electrochemical redox reaction of the excessive carriers with the ions on the surface of the CdSe/CdS (core/shell) QD. Figure 2 (f) shows the concept of the electrochemical-inert ligand exchange.…”
Section: Synthesis Of Qd Materialsmentioning
confidence: 99%
“…QDs have ultra-high porous structure, wide surface area, lower electrochemical behavior (higher analytical signal), flexible structure, high electrical and chemical function, etc. [ 161 , 162 ]. The design of developed electrochemical biosensors can be using QDs with such special characteristics [ 163 , 164 ].…”
Section: Nanomaterials Towards Diagnosis and Biosensing Of Prostatmentioning
confidence: 99%